Anayasa Mahkemesi’nin tutuklama kararının maddi şartları içtihadına eleştirel bir yaklaşım - Sevdiren, Öznur (Anayasa Hukuku Dergisi, 2019)
ÖZET: Anayasa MahkemeVi¶nin özgürlük ve güvenlik hakkÕnÕn ihlali iddialaUÕ ile ilgili \aSÕlan bireysel baúYXUXlaUda, konu ile ilgili iç hukuk meY]XaWÕ ve Avrupa ønVan HaklaUÕ MahkemeVi¶nin ioWihadÕ\la muhtelif biçimlerde ba÷daúma\an bir içtihat birikimi \aUaWWÕ÷Õ gözlemlenmektedir. Birincisi, Anayasa Mahkemesi, keyfi tutma \aVa÷Õna kaUúÕ temel bir güvence olXúWXUan ve Anayasa md. 19¶da özgürlük ve güvenlik hakkÕnÕn VÕnÕUlanmaVÕ için temel bir koúXl olarak görülen µkXYYeWli beliUWi¶ kavramÕnÕ, AøHM ioWihaWlaUÕndan yola oÕkaUak kendi SUaWi÷ine µinandÕUÕcÕ delil¶ olarak tercüme etmektedir. Mahkeme¶nin µinandÕUÕcÕ' delil kaYUamÕna izafe eWWi÷i ú She seviyesi iç hukuktaki µkXYYeWli suç ú SheVini gösteren somut delilleU¶ ölçütünden daha d ú kW U. Öte yandan, Mahkeme, tutuklama nedenlerinin ilk tutuklama kaUaUÕndan itibaren zorunlu oldX÷X yönündeki iç hukuk düzenlemelerini göz aUdÕ ederek AøHM¶nin Letellier prensibi olarak da bilinen sürecin ilerlemesi ile birlikte µilgili ve yeterli geUekoe¶ bildirme zorunlu oldX÷X yönündeki ioWihadÕna VÕklÕkla iúaUeW etmektedir. ølginoWiU, AøHM¶nin Buzadji kaUaUÕ VonUaVÕ da Anayasa MahkemeVi¶nin ioWihadÕnda bu yönde bir de÷iúiklik söz konusu de÷ildiU. Bu ba÷lamda, katalog suçlar söz konusu oldX÷Xnda da, Mahkeme, Anayasa md. 19¶da baúWa ölçülülük dâhil olmak üzere öngörülen güvenceleri etkisiz hale getirecek bir yorumu benimsemektedir. Nihayet, Anayasa Mahkemesi ola÷an VW hal ile ilgili verilen tutuklama kaUaUlaUÕnÕ ise, aoÕkoa bir yasal dayanak olmakVÕ]Õn yorum yoluyla, ola÷an VW hallerde temel hak ve özgürlükler rejiminin d ]enlendi÷i 15. madde çerçevesinde ele almakWadÕU. AøHM, Anayasa MahkemeVi¶nin söz konusu SUaWi÷inin AøHS ile ba÷daúmadÕ÷ÕnÕ hali ha]ÕUda hüküm alWÕna almÕú bulunmaktadÕU. Bu oalÕúma, Anayasa MahkemeVi¶nin her üç yönden YeUdi÷i kararlarla, Mahkeme¶nin, konu ile ilgili iç hukuku VÕnÕUla\ÕcÕ bir biçimde yorumladÕ÷ÕnÕ ve bu durumun gerek AøHS md. 5¶Weki iç hukuka uygunluk koúXlX gerekse S|]leúme¶nin 53. maddesine a\kÕUÕ oldX÷XnX tespit etmektedir.

ABSTRACT: In individual applications claiming a violation of the right to liberty and security, the Constitutional Court adopt an approach in various aspects conflicting the basic precepts of domestic law and the case law of the ECtHR. First, as a principal requirement of the deprivation of liberty, the existence of µstrong presumption¶ that an individual has committed a crime constitutes a vital safeguard against the prohibition on the arbitrary detention. In the case law of the Constitutional Court, the µstrong presumption¶ requirement in Article 19 of the Turkish Constitution has been translated into µconvincing (reasonable) evidence¶. The degree of suspicion attributed to the concept of convincing evidence is evidently much lower than that of the criterion on strong suspicion. On the other hand, notwithstanding the fact that Turkish law requires the judge and courts from the first decision of remand in custody also to substantiate the risk of absconding or the destruction or alteration of evidence, the Constitutional Court effectively disregards such requirements. Instead, inspired, by the previous ECHR case law, the Court has consistently ruled related and sufficient reasons for the remand decision need not to be given until after a certain period of time elapsed. Intriguingly, no change has occurred in the Court¶s case law, after Buzadji. This problem has been aggravated by the problem of the so called catalogue offences where the legislature established ostensibly a legal assumption that the reasons laid down in the Constitution and the Turkish Criminal Procedure Code for detention exists. Hitherto, the Court adopted an approach, which has essentially impaired the safeguards enshrined in Article 19 of the Constitution including the principle of proportionality. Finally, as to the custody on remand decisions relating to public emergency caused by the attempted coup, the Court, with its own interpretation without having any legal basis, makes its assessment based on Article 15 of the Turkish Constitution. Recently, the ECtHR found this approach inadmissible. By examining the case law of the Turkish Constitutional Court, this study argues that in its jurisprudence in all three respects, the Court has so far interpreted domestic law in a very restrictive manner. Beyond doubt this itself constitutes a violation of Article 5 making explicitly reference to domestic law and Article 53 of the Convention.
A critical approach to the case law of the Constitutional Court in relation to the substantive requirements of remand in custody decision
Keywords: tutuklama; tutuklama nedenleri; katalog suçlar (CMK md. 100/3); olağanüstü hal; özgürlük ve güvenlik hakkı; remand in custody; grounds for remand in custody; catalogue offences (Article 100/3 of the Turkish CPC); emergency law and the right to liberty and security